PENGARUH KUALITAS PRODUK, CITRA MEREK, PERSEPSI RESIKO, RIVIEW PELANGGAN DAN KEPERCAYAAN TERHADAP KEPUTUSAN PEMBELIAN PADA E-COMMERCE TIKTOKSHOP - Silvi Nor Anggraeni; M. Ariya Eka Setiawan; Siska Maya Mein Dewinda; Rizka Damayanti; Muhammad Choirul Latif (Prosiding SEMANIS: Seminar Manajemen Bisnis, 2025)
This study aims to analyze the effect of product quality, brand image, risk perception, customer reviews, and trust on purchasing decisions on the TikTok Shop e-commerce platform, with a focus on Generation Z in Bojonegoro. Using quantitative methods with linear regression analysis, this study involved 66 respondents selected through purposive sampling technique. The results showed that product quality, brand image, customer reviews, and trust have a positive and significant influence on purchasing decisions, while risk perception is not significant. These findings indicate that quality factors, brand image, and customer reviews play an important role in driving purchases. The implications of this study emphasize the importance of maintaining product quality, strengthening brand image, reducing risk perception, managing customer reviews, and increasing consumer trust. With these strategies, businesses in TikTok Shop can maximize opportunities in an increasingly competitive e-commerce market